Factors associated with the consumption of ultra-processed food by Brazilian adolescents: National Survey of School Health, 2015 - Janiquelli Barbosa Silva; Bianca Caroline Elias; Sarah Warkentin; Laís Amaral Mais; Tulio Konstantyner
ABSTRACT Objective: To identify the prevalence and factors associated with the consumption of ultra-processed foods by Brazilian adolescents. Methods: The sample was representative of adolescents and participants in the cross-sectional population-based study National Survey of School Health, 2015 edition (PeNSE-2015). A self-administered questionnaire was used for data collection. The variable weekly consumption of ultra-processed foods was considered, and consumption more than seven times a week was considered excessive. Descriptive and inferential analyses of demographic, socioeconomic, behavioral and environmental characteristics potentially associated with the outcome were performed. Poisson's multiple regression model was adjusted to control for confounding factors. Results: The prevalence of excessive consumption of ultra-processed foods among 16,324 adolescents in Brazil was 75.4%. Nine factors independently associated with this outcome were identified: age under 15 years (RR 1.08; p<0.001), daily sitting time greater than four hours (RR 1.13; p<0.001), eating while watching TV or studying more than four days a week (RR 1.09; p<0.001), daily TV time greater than three hours (RR 1.08; p<0.001), breakfast frequency less than four days a week (RR 1,03; p=0.001), having a cell phone (RR 1.12; p<0.001), absent maternal education (RR 0.88; p<0.001), being enrolled in a private school (RR 1.05; p=0.002) located in the urban area (RR 1.13; p=0.002). Conclusions: The results express the multifactorial characteristic of excessive consumption of ultra-processed foods and suggest the need for the development and implementation of health policies to guide the consumption of these foods and the importance of adopting healthy behaviors for this population group in both school and home environments.